Puerto Rico: The collapse of a country. An initial reflection on the debacle of the sugar industry, petrochemicals and section 936. - Aleman Iglesias, Javier (2020)
In the following work we have as a central objective to examine the socio-economic implications of the disintegration of the economy of Puerto Rico from the second half of the twentieth century, using as a center of study the cases of the sugar industry, the petrochemical industry -CORCO and the industries under the section 936 sector. The three sectors were at their peak the most important activities in the Puerto Rican economy during the twentieth century; However, the three sectors were displaced and ruined by local and international situations, causing one of the largest economic crises in our contemporary history.